Proposed Marketing Strategy of Gang Nikmat (The Indonesian Journal of Business Administration, 2021)
In the current era, culinary business isn’t only limited to fulfill the human primary needs but also part of a lifestyle so it needs a more supporting medium to actually compete in the current business. Bandung is one of the more famous tourist cities because of its high creativity. The culinary business potential in Bandung still continues to grow. This is backed up by the number of contributions done by the culinary business as the 3rd biggest contributor in its Gross Domestic Product (GDP) in Bandung (BPS Kota Bandung, 2019). Gang Nikmat, as one of the culinary businesses in Bandung, wants to continuously contribute to the culinary business development in Bandung while still highlighting the “modern alley” concept in Bandung. Gang Nikmat offers a fusion of Asian-Indonesian food products. The high rivalry in culinary business pushes Gang Nikmat to have the right strategy to maintain itself and continuously develop. This research is a way to know an effective marketing strategy to improve the relationship with the customers and improve the sales figures of Gang Nikmat using a quantitative method. To analyze the current condition of the company itself, literature review is implemented to the internal analysis and external analysis. Gang Nikmat implements the Porter Value Chain and Existing BMC for its internal analysis, whilst Customer Analysis, Competitor Analysis and Porter's Five Forces is used for external analysis. Gang Nikmat uses a quantitative method with a questionnaire to 100 respondent who visited Gang Nikmat. After the value is acquired, internally and externally, a quadrant position is produced inside of the SWOT to decide on which development is needed going forward. Based on research exploration, Gang Nikmat is being demanded to do an aggressive strategy like market development, market penetration and product development to improve relationships with customers and improve sales figures.Keyword: Culinary Business, BMC, Quantitative Method, Sales, Porter’s Five Force, Porter Value Chain, Quadrant